Pengaruh Variasi Waktu Curing Pada Kegagalan Uji Bending Komposit Sandwich Serat Karbon Dengan Core PVC Foam - Fajar Paundra; Joy Rivaldo Aritonang; Eko Pujiyulianto; Abdul Abdul; Puguh Elmiawan (P3M Politeknik Negeri Cilacap, 2025)
Curing is a method used to enhance the performance of composite materials by heating them in an electric oven for a specific duration and at a controlled temperature. This study aims to examine the effect of curing time variations on the failure analysis of carbon fiber sandwich composites with a PVC foam core under bending tests. The materials used in this research include polyester resin, 240 gsm carbon twill fiber, and a 5 mm thick PVC foam core. The manufacturing method applied was vacuum bagging, followed by a curing process with time variations of 30 minutes, 60 minutes, 90 minutes, and 120 minutes at a constant holding temperature of 80Â°C. Bending tests were carried out according to ASTM C393 standards. The highest bending strength of the sandwich composite was achieved with a curing time of 120 minutes, reaching 45.55 MPa, while the lowest strength was observed in the specimen without curing, at 25.76 MPa. The failures observed after bending tests included core failures such as core crush, indentation, and delamination, as well as skin failures like micro buckling.